THE MORPHOLOGICAL BALANCE BETWEEN ACCEPTANCE AND REJECTION THE INTRODUCTION (CAHIERS MAGELLANES-NS, 2024)
The morphological level is considered one of the most important levels of linguistic sciences that received the attention of researchers through their studies of it, and it was almost the beginning of those studies when they realized that this lesson would be delayed until after the science of grammar, and the book of Sibawayh (d. 180 AH) - which was the first book to collect... It contains Arabic sciences - the best evidence of that.